Readings on equitable policing, human variation and social justice - Abdul-Ra'uf, Bakhitah B. (Cognella, 2023)
Readings on Equitable Policing, Human Variation, and Social Justice provides students with a carefully selected collection of articles that identify and address ways to improve the relationship and understanding between African American inner-city communities and the police. The reader is organized into six distinct units. Unit I introduces students to the concept of human variation, the range of possible values for any characteristic, physical or mental, of human beings. In Unit II, readings explore issues of race, ethnicity, and inequality in America. Unit III covers American ethnocentrism and western norms. Unit IV features readings about stereotyping Africans and the African diaspora. This unit includes readings that address the ways in which people of color are portrayed in the media, how stereotypes in American culture can also influence police stereotypes and predictions, and more. The final two units examine social control, crime control, and social order; racial profiling by law enforcement officials; the perception of the police by citizens; and the implications of social structures and concepts on social justice and equality. Providing students with a relevant and timely examination of police-community relations, Readings on Equitable Policing, Human Variation, and Social Justice is an excellent resource for courses and programs in criminal justice and policing